Peripheral venous catheter collection of immune effector cells and hematopoietic stem cells is feasible and safe in older pediatric patients. Issue 12 (9th November 2021) - Livingston, Joel; Di‐Mola, Maria; Lowry, Jane; Ruse, Nigel; Chiang, Kuang‐Yueh; Chopra, Yogi; Schechter, Tal; Ali, Muhammad; Licht, Christoph; Wall, Donna; Krueger, Joerg
Abstract: Background: The Collection of hematopoietic stem cells (HSC) and immune effector cells (IEC) has unique challenges in children. To maintain adequate blood flow, central venous catheters (CVCs) remain the standard of care in many centers, but are associated with procedural risks and increased resource utilization. The goal of this study was to determine feasibility and safety of peripheral venous catheter (PVC) cell collection in older children. Methods: Patients and donors requiring venous access with weight >25 kg, age >8 years were screened for PVC collection via 18G PVCs. Those with poor venous access (on history/exam/pre‐screening ultrasound) or unable to maintain suitable procedural position were excluded. Comparison was made to CVC collections in a matched patient cohort. Results: Thirty‐eight individuals were screened and met age/weight criteria for PVC collection. Five did not have PVC collection attempted due to poor access ( n  = 4) or behavioral concerns ( n  = 1). Thirty‐three had PVC collection attempt (HSC = 22; IEC = 11) with median age 15.3 year (range 9.7–18.0) and weight 58.5 kg (range 27.9–115.4). Thirty‐two of 33 (97%) patients were collected successfully by PVC without adverse events. Comparing PVC to matched CVC collection cohort ( n  = 18), there was no significant difference in flow rate (48.2 mL/h vs 53.9 mL/h, p = 0.12), collection time (266 min vs 262 min, p = 0.85) or collection efficiency (IEC/CD3 60.9% vs 60.8% p = 0.99; HSC/CD34 53.6% vs 41.3% p = 0.05). Conclusion: PVC collection of HSC and IEC is feasible and safe in older children with comparable collection efficiency to CVC collections. Ultrasound screening may reduce failure rates. PVC collections can reduce the risk of CVC insertions and associated healthcare costs.